Mindfulness-based intervention on Chinese patients with amphetamine-type stimulant use disorders: an EEG functional connectivity study - Zhang, Jingying; Chen, Tianzhen; Tan, Haoye; Wu, Qianying; Chen, Liyu; Yuan, Chenxin; Ding, Xinni; Zhang, Lei; Du, Chao; Li, Jun; Lu, Erfeng; Wu, Yanru; et al. (Mindfulness, 2022)
Amphetamine-type stimulants (ATS) have become the most used drugs in China, and increasing evidence indicates that ATS can induce a series of cognitive deficits, including impacts to functional connectivity (FC). This study investigates FC defects among ATS patients in China, and examines the mechanism and effects of a 10-day abbreviated mindfulness-based relapse prevention (MBRP) program with electroencephalography (EEG).